Waveform-regulated catalyst-free NOx removal in micro-hollow surface dielectric barrier discharge - Mengwei Sun; Dingkun Yuan; Zhongqian Ling; Fawei Lin; Guangxue Zhang; Shahong Zhu (Journal of Environmental Chemical Engineering, 2026)

Molecular engineering for bitterness masking of natural products: from decoding structure-taste relationships to structure-driven bitterness suppression - Linjie Tian; Jiao Song; Jiaxin Li; Jing Wu; Haozhou Huang; Junzhi Lin; Li Han; Hongyan Ma; Dingkun Zhang (Critical Reviews in Food Science and Nutrition, 2026)

Comparative analysis of laminar burning velocity of CH4 + H2 flame across a broad temperature range under atmospheric pressure - Jiayi Lin; Zhongqian Ling; Leilei Liu; Ye Yuan; Jiamin Li; Dingkun Yuan; Jiangrong Xu; Xinlu Han; Zhihua Wang (Fuel, 2026)

Instant gel-forming microcapsules based on micronized-κ-carrageenan for bitter taste quenching bioinspired by the passion fruit seed - Jiao Song; Linjie Tian; Shuyu Deng; Yifei Zhang; Junzhi Lin; Zhiping Guo; Hongyan Ma; Dingkun Zhang; Li Han; Zhimin Ci (Carbohydrate Polymers, 2026)

The Combination of Sodium Tanshinone IIA Sulfonate and Mesenchymal Stem Cell-derived Exosomes Against Spinal Cord Injury via VEGF Pathway - Dan Luo; Lin Ma; Zhijian Pan; Ling Chen; Zhifeng Hu; Chaolun Liang; Zenglu Wang; Zhifeng Xiao; Dingkun Lin; Jinfeng Li; Da Guo; Xing Li (Molecular Neurobiology, 2026)

A systematic analysis of the sensory qualities of Asparagus cochinchinensis (lour.) Merr. From the four major production areas in China: Sensory characteristics, key flavor substances, and molecular mechanisms of flavor formation - Jingping Zhong; Shuyu Deng; Mengqi Li; Honglin Yin; Xinming Chen; Zhiyan Deng; Xiaoming Bao; Qingchu Tan; Junzhi Lin; Dingkun Zhang; Gang Shen; Li Han; et al. (Food Chemistry, 2025)

Molecular mechanisms of bone metastasis in breast cancer based on transcriptomic and microbiomic analysis - Dihui Zhang; Manli Long; Lingcui Meng; Yongjin Li; Bolai Chen; Dingkun Lin; Guoyi Su (Cancer Causes & Control, 2025)

Nano Sim@ZIF8@PDA modified injectable temperature sensitive nanocomposite hydrogel for photothermal/drug therapy for peri-implantitis - Dingkun Liu; Jinbing Chen; Linjuan Gao; Xing Chen; Liujun Lin; Yuan Liu; Xia Wei; Yu Pan; Yinghui Wang; Hui Cheng (Carbohydrate Polymers, 2025)

Curculigoside Regulates Apoptosis and Oxidative Stress Against Spinal Cord Injury by Modulating the Nrf-2/NQO-1 Signaling Pathway In Vitro and In Vivo - Yu Hou; Chaolun Liang; Lili Sui; Yang Li; Kai Wang; Xing Li; Kunrui Zheng; Haitao Su; Dianweng Xie; Dingkun Lin; Da Guo; Le Wang (Molecular Neurobiology, 2025)

Transplantation of Wnt5a-modified Bone Marrow Mesenchymal Stem Cells Promotes Recovery After Spinal Cord Injury via the PI3K/AKT Pathway - Haimei Yang; Chaolun Liang; Junhua Luo; Xiuzhen Liu; Wanshun Wang; Kunrui Zheng; Dan Luo; Yu Hou; Da Guo; Dingkun Lin; Xiasheng Zheng; Xing Li (Molecular Neurobiology, 2024)
Spinal cord injury (SCI) is a severe neurological condition that can lead to paralysis or even death. This study explored the potential benefits of bone marrow mesenchymal stem cell (BMSC) transplantation for repairing SCI. BMSCs also differentiate into astrocytes within damaged spinal cord tissues hindering the cell transplantation efficacy, therefore it is crucial to enhance their neuronal differentiation rate to facilitate spinal cord repair. Wnt5a, an upstream protein in the non-classical Wnt signaling pathway, has been implicated in stem cell migration, differentiation, and neurite formation but its role in the neuronal differentiation of BMSCs remains unclear. Thus, this study investigated the role and underlying mechanisms of Wnt5a in promoting neuronal differentiation of BMSCs both in vivo and in vitro. Wnt5a enhanced neuronal differentiation of BMSCs in vitro while reducing astrocyte differentiation. Additionally, high-throughput RNA sequencing revealed a correlation between Wnt5a and phosphoinositide 3-kinase (PI3K)/protein kinase B(AKT) signaling, which was confirmed by the use of the PI3K inhibitor LY294002 to reverse the effects of Wnt5a on BMSC neuronal differentiation. Furthermore, transplantation of Wnt5a-modified BMSCs into SCI rats effectively improved the histomorphology (Hematoxylin and eosin [H&E], Nissl and Luxol Fast Blue [LFB] staining), motor function scores (Footprint test and Basso-Beattie-Bresnahan [BBB]scores)and promoted neuron production, axonal formation, and remodeling of myelin sheaths (microtubule associated protein-2 [MAP-2], growth-associated protein 43 [GAP43], myelin basic protein [MBP]), while reducing astrocyte production (glial fibrillary acidic protein [GFAP]). Therefore, targeting the Wnt5a/PI3K/AKT pathway could enhance BMSC transplantation for SCI treatment.

Comparison and identification of aroma components in 21 kinds of frankincense with variety and region based on the odor intensity characteristic spectrum constructed by HS–SPME–GC–MS combined with E-nose - Xinming Chen; Dandan Yang; Lin Huang; Mengqi Li; Jihai Gao; Can Liu; Xiaoming Bao; Zhizhi Huang; Jinhui Yang; Haozhou Huang; Dingkun Zhang; Runchun Xu (Food Research International, 2024)

Study on the mechanism of natural polysaccharides on the deastringent effect of Triphala extract - Jun Liu; Pinhu Wang; Haozhou Huang; Xingliang Xie; Junzhi Lin; Youde Zheng; Li Han; Xue Han; Dingkun Zhang (Food Chemistry, 2024)

Comparative study by microwave pyrolysis and conventional pyrolysis of pharmaceutical sludge: Resourceful disposal and antibiotic adsorption - Yifan Zhou; Fawei Lin; Zhongqian Ling; Mingxiu Zhan; Guangxue Zhang; Dingkun Yuan (Journal of Hazardous Materials, 2024)

Transplantation of MiR-28-5p-Modified BMSCs Promotes Functional Recovery After Spinal Cord Injury - Zhen Li; Haitao Su; Guandai Lin; Kai Wang; Yongming Huang; Yaqian Wen; Dan Luo; Yu Hou; Xuewei Cao; Jiaxian Weng; Dingkun Lin; Le Wang; et al. (Molecular Neurobiology, 2024)
Traumatic spinal cord injury (TSCI) is a prevalent central nervous system condition that imposes a significant burden on both families and society, affecting more than 2 million people worldwide. Recently, there has been increasing interest in bone marrow mesenchymal stem cell (BMSC) transplantation as a promising treatment for spinal cord injury (SCI) due to their accessibility and low immunogenicity. However, the mere transplantation of BMSCs has limited capacity to directly participate in the repair of host spinal cord nerve function. MiR-28-5p, identified as a key differentially expressed miRNA in spinal cord ischemia–reperfusion injury, exhibits differential expression and regulation in various neurological diseases. Nevertheless, its involvement in this process and its specific regulatory mechanisms in SCI remain unclear. Therefore, this study aimed to investigate the potential mechanisms through which miR-28-5p promotes the neuronal differentiation of BMSCs both in vivo and in vitro. Our results indicate that miR-28-5p may directly target Notch1, thereby facilitating the neuronal differentiation of BMSCs in vitro . Furthermore, the transplantation of lentivirus-mediated miR-28-5p-overexpressed BMSCs into SCI rats effectively improved footprint tests and Basso, Beattie, and Bresnahan (BBB) scores, ameliorated histological morphology (hematoxylin–eosin [HE] and Nissl staining), promoted axonal regeneration (MAP2 and growth-associated protein 43 [GAP43]), and facilitated axonal remyelination (myelin basic protein [MBP]). These findings may suggest that miR-28-5p-modified BMSCs could serve as a therapeutic target to enhance the behavioral and neurological recovery of SCI rats.

Discovery and verification of bitter components in Panax notoginseng based on the integrated strategy of pharmacophore model, system separation and bitter tracing technology - Jing Yang; Min Qiu; Tai Lu; Shangdong Yang; Ji Yu; Junzhi Lin; Hongyan Ma; Zhiping Guo; Zhencai Chen; Xue Han; Dingkun Zhang (Food Chemistry, 2023)

Review of low-temperature plasma nitrogen fixation technology - Hang Chen; Dingkun Yuan; Angjian Wu; Xiaoqing Lin; Xiaodong Li (Waste Disposal & Sustainable Energy, 2021)

Revision surgery after instrumental fixation in patient with butterfly vertebra: a case report - Jiheng Zhan; Yufeng Wang; Bolai Chen; Dingkun Lin (Acta Neurologica Belgica, 2020)

Synthesis and biological evaluation of n-butylphthalide derivatives as anti-platelet aggregation agents - Meihui Chen; Qi Liu; Min Tan; Shijun Wen; Rongbiao Pi; Dingkun Lin (Natural Product Research, 2016)